Characteristics of Changes in the Postnatal Ontogenesis of the Egg Path of Different Breeds - Tangirov Qayum Jo‘rayevich; Achilov Shamsiddin Amanovich; Mallayev Muhriddin G‘ofur o‘g‘li (Central Asian Journal of Theoretical and Applied Science, 2022)
The dynamics of changes in the linear dimensions of the right and left ovarian pathways of ewes of different age and karakul breed were studied, and it was found that the absolute indicators show specific changes during the physiological stages of postnatal ontogeny. Absolute lengths of the right and left ovarian pathways were observed to increase rapidly during the first 3 months of postnatal development, with peak peaks occurring at 18 and 36 months of age. Absolute rates of ovulation, especially after 18 months of age, have been reported to be slightly lower in karakul sheep than in ewes.